Facile synthesis of strontium copper phosphate (SrCuPO4) binary composite for the high-performance supercapattery devices - Zaka, Asma; Iqbal, Muhammad Waqas; Afzal, Amir Muhammad; Hassan, Haseebul; Alzahrani, Huda A.; Yasmeen, Aneeqa; Abbas, Tasawar; Aftab, Sikandar; Neffati, R. (Journal of materials science. Materials in electronics, 2022)
Supercapattery combines the properties of supercapacitors and batteries and has excellent energy and power densities. It has gotten much attention as compared to supercapacitors and batteries because of its high energy storage capability and stability. To design a supercapattery device, the strontium phosphate, copper phosphate, and their three composites with different weight ratios such as Sr 0.75 Cu 0.25 PO 4 , Sr 0.5.0, Cu 0.50 PO 4, and Sr 0.25 Cu 0.75 PO 4 and named as S 1 , S 2, and S 3 were synthesized using a hydrothermal approach. X-ray diffraction and scanning electron microscopy to examine the structural characterization as well as the surface morphology of all the samples. More specific capacity was calculated for all the samples, and found that the specific capacity having its maximum value of 856 C/g at 2.0 A/g was attributed to S 1 sample due to the overall effect of strontium with copper. The hybrid device S 2 was also prepared using activated carbon which is considered a positive electrode, while S 2 worked as a negative electrode. SrCuPo 4 has an estimated power density of 793.92 W/Kg, the energy density is 31.4 Wh/Kg. A reliability measurement was performed on this real device for assessing stability, and after 1000 charging/discharging cycles, it was observed that 87 percent of the initial capacity was retained. Thus strontium copper phosphate can help us in the future for industrial applications of supercapattery for high energy density and power density.